ISOLASI DAN IDENTIFIKASI BEBERAPA KOMPONEN KIMIA EKSTRAK DIETIL ETER STANDAR HERBA Oxalis corniculata L. - Herwin Herwin; Rachmat Kosman; Muzakkir Baits (Fakultas Farmasi UMI, 2014)
A research have been conducted about isolation and identification some chemicals components in diethyl ether standard ekstract of Oxalis corniculata L. herb from Mamuju of West Sulawesi with purpose isolation and identification some chemicals components standard ekstract diethyl ether Oxalis corniculata L. herb based on fitochemistri parameters on the way kualitatife dan kuantitatife. Based on isolation with fitochemistri parameters of kuantitatife that standard diethyl ether ekstract 38 gram. Based on isolation and identification some chemical components obtained that dietyl ether ekstract of thin layer cromatography obtained chemicals components flavanoid at Rf 0.47 value with reagent Antimo (III) cloride, components alcaloids at Rf 0.86 value with reagents chemicals dragendorf, components chemicals steroids at Rf 0.90 with reagents chemicals Liebermann-Bouchard and kualitatife analisis at specific parameter in organoleptic that colour ekstract green, aromatis, smell, a tick form idication obtained alcaloids, steroids and flavanoids.